A new SmartSMS protocol for secure SMS communication in m-health environment. (January 2018) - Vijayakumar, P.; Ganesh, S. Milton; Deborah, L. Jegatha; Rawal, Bharat S.
Abstract: In the present m-health scenario, a patient and a doctor may engage in an SMS conversation regarding the sensitive medical information about the body of a patient and the corresponding treatment for it. Hence, designing a secure protocol for SMS communication for this context of m-health has become mandatory. Though a number of protocols have been defined in the literature, each protocol exposes some drawbacks which makes it unsuitable for the secure SMS communication. Protocols proposed earlier such as SMSSec, PK-SIM have more computation and communication overheads. Despite being secure, EasySMS protocol suffers from Denial of Service (DoS) attacks and Distributed Denial of Service (DDoS) attacks. Thus, an efficient protocol called SmartSMS to ensure the end-to-end secure SMS communication in m-health environment while being resistant to attacks has been proposed in this work. The main contribution of this proposed SmartSMS protocol is to minimize the computational complexity of the Mobile Station (MS) and the Authentication Server (AS). In addition, the proposed work also minimizes the communication complexity involved in secure SMS communications. Through extensive simulations, it has been proved that the proposed protocol shows lower computational and communication overheads compared to other protocols in the literature and shows promising results.